A circadian transcriptional subnetwork and EARLY FLOWERING 3 control timing of senescence and grain nutrition in bread wheat - Buckley, Christopher R.; Boyte, Joshua M.; Liu, Yalin; Albiston, Robert L.; Hyles, Jessica; Beasley, Jesse T.; Johnson, Alexander A.T.; Trevaskis, Ben; Fournier‐Level, Alexandre; Haydon, Michael J. (The New phytologist, 2025)
Summary Circadian clocks control daily and seasonal timing of physiology and development. Because of their influence on photoperiodic flowering, variants in circadian clock genes have been selected for phenology during domestication of cereal crops. To explore the potential impact of this genetic variation on circadian‐regulated traits, we investigated the relationship between the circadian clock and leaf senescence in hexaploid bread wheat. We phenotyped a collection of elite wheat cultivars for circadian rhythms, senescence and grain nutrition and used genotypes of multiple circadian clock genes to assign cultivars to circadian multilocus genotypes (MLGs). We compared the circadian‐regulated transcriptomes in mature and senescent leaves by RNA sequencing and used near‐isogenic lines (NILs) of a deletion in EARLY FLOWERING 3‐D1 (ELF3‐D1), a known phenology locus, to test for a functional contribution to the timing of senescence and grain protein content (GPC). We detected variation in circadian rhythms between wheat cultivars, which was significantly associated with the timing of senescence. We revealed substantial reorganisation of the circadian‐regulated transcriptome during senescence and identified a transcriptional subnetwork representing a link between the circadian oscillator and regulators of leaf senescence. NILs of an ELF3‐D1 deletion confirmed a significant effect on the timing of senescence and GPC. Our results demonstrate an important role for the circadian clock in controlling the timing of senescence in wheat, which highlights potential consequences of circadian clock genes selected for phenology on other valuable crop traits.